The Open-mindedness for University Professors - Raheem Mohammed, Marwa; Majeed Al- Attabi, Abdullah (Journal of College of Education, 2024)
The goal of research is to identify the following:-1-      The level of open-mindedness to university professors.2-      The concept of statistical differences of open-mindedness for university professors in accordance with variety of genders (male – female), and academic specialization (scientific – educational).Frame of Research1-      Objectivity– (open-mindedness of University Professors)2-      Location – (University of Wasit)3-      Human Resources– (Wasit University Professors)4-      Time framework – 2021 – 2022 academic year. Methodology of ResearchThe researcher follows the narrative and relational methodology since they fit with the nature and goals of research.Research CommunityThe community of current research consists of 949 professors in university of Wasit in both genders (male & female), additional to the academic specialty (scientific, educational) .Research SamplesThe sample of research is 774 professors (male & Female), in both scientific and educational academic specialization.Research Material  The measurement of Open-mindedness The researcher has prepared the articles of measurement of open-mindedness for university professors. They are 30 articles in their initial draft. The alternative response is ( always, almost, sometimes, seldom and never). The scales are respectively (1,2,3,4,5 and 6).The psycho-meter characteristics of scale :Honesty and Persistence are the main characteristics of the new measurement tool. The researcher has taken the virtual honesty and constructive honesty for the measurement. Persistence has been calculated based on test, retest and Cronbach Alpha.Results:1-      Research sample obtains good level of Open-mindedness.2-      There’s variety based on genders (male – female), the result is in the favor of male gender.3-      There is difference in the open-mindedness relationship based on the specialty (scientific – educational), the result is in the favor of scientific specialty.A number of suggestions and recommendations were made by the researcher based on the results the current research has reached.
Keywords: Open- mindedness University Professors